Responsibility and Role of Hospitals in Efforts to Resolve Medical Disputes over Surgical Procedures for Children Suffering from Tumors (Study at H. Adam Malik Hospital Medan) - Dwiki Ahmad Syaufi; Redyanto Sidi; Marice Simarmata (Fakultas Hukum Dehasen, 2026)
Surgical procedures in children with tumors constitute high-risk medical services that have the potential to give rise to medical disputes. Within the framework of health law, hospitals function not only as healthcare providers but also as legal entities responsible for service quality, patient safety, and the resolution of medical disputes. This study aims to analyze the legal responsibilities and roles of hospitals in resolving medical disputes arising from pediatric surgical procedures in children with tumors, based on Minister of Health Regulation Number 24 of 2022, Law Number 17 of 2023 on Health, and Government Regulation Number 28 of 2024. The research employs normative and empirical juridical approaches, supported by field studies conducted at H. Adam Malik General Hospital, Medan. The findings indicate that hospital legal responsibility is comprehensive, encompassing the actions of medical personnel, healthcare service systems, compliance with patient safety standards, and medical record documentation. Hospitals also play a strategic role in resolving medical disputes through non-litigation mechanisms, particularly internal mediation and patient complaint systems, in order to provide legal protection and prevent the escalation of disputes.